Avaliação da eficácia da membrana semipermeável na pele de recém-nascido prematuro como recurso tecnológico para prevenção de perdas de água transepidérmicas - Gurgel, Eloah de Paula Pessoa (2015)
The neonatal population represents a strategic group as regards the reduction of infant mortality. Therefore, it becomes a challenge for the team assisting these patients to keep them stable with their vital functions in balance, since important changes occur during fetal life and after birth, especially in preterm infants. This study aimed to evaluate the efficacy of using the semipermeable membrane as technological resource applied in different areas of the preterm infants’ skin seeking to reduce transepidermal water loss. Seventy-two preterm infants underwent an experimental study, randomly distributed into four groups to receive the semipermeable membrane in different areas essential for application: thorax, abdomen and lower extremities. It took place at the Neonatal Intensive Care Unit (NICU) of the Maternity School Assis Chateaubriand (MEAC) in the city of Fortaleza, Ceará, Brazil. The sample consisted of preterm infants who met the following inclusion criteria: weight ≤ 1,500 grams and gestational age ≤ 32 weeks; remain in the unit for seven days; not show any severe malformations that affect skin integrity. We excluded infants with weakened health that prevented completion of the study; patients with congenital malformations, such as gastroschisis, omphalocele or myelomeningocele; and the consent given by parents and/or guardians of preterm infants. As outcome variables, we considered sodium, glucose, urine specific gravity, weight, and fluid loss. Gender and gestational age constituted the main variables of the experiment baseline. Fluid losses were measured with the aid of Tewameter applied to the skin of preterm infants, for 30 seconds. Data were compiled into Excel and statistical analysis with the software support R 2 version. 12. 1. In this study, we used a significance level of 5% and presented the data in tables. The ethical recommendations were followed during the research steps. Preterm infants were admitted to the Obstetric Center and the main medical diagnoses were prematurity, respiratory distress syndrome, and hyaline membrane disease. In total, preterm infants of the four groups were kept in humidified double walled incubators (100%), under mechanical ventilation (86.84%), nasal CPAP (7.89%), and use of intravenous hydration through central access (100%). They used antibiotics and parenteral nutrition (100%), enteral nutrition (7.89%), and phototherapy (68.42%). Applying the semipermeable membrane, soon after birth, was effective with regard to the maintenance of sodium, water quota, urine density, and glucose. Transepidermal loss was lower in the group that used the semipermeable membrane along the body extension, but it was not statistically different from those in which the membrane was applied to the thorax and abdomen (Group 3). In turn, this group presented lower blood glucose levels than the groups who had the membrane applied in the lower limbs and the thorax or abdomen (Groups 1, 2 and 3), but not different from newborns who used it along the body extension (Group 4). Furthermore, the intragroup changes observed in the following period among the six variables in study were similar in the four groups. This way, there are indications that using the semipermeable membrane applied to the thorax and abdomen may have a similar effect to its use along the body extension. Nonetheless, it should be noted that the small sample size might have contributed to failure to detect statistical differences, thus these results should be considered.